Simeprevir plus peginterferon/ribavirin for HCV genotype 1‐infected treatment‐naïve patients in China and South Korea. Issue 5 (May 2016) - Wei, Lai; Han, Tao; Yang, Dongliang; Heo, Jeong; Shang, Jia; Cheng, Jun; Chen, Xinyue; Xie, Qing; Kim, Ju‐Hyun; Kalmeijer, Ronald; Ouwerkerk‐Mahadevan, Sivi; Hoeben, Eva; et al.
Abstract: Background and Aim: Approximately one‐third of patients with hepatitis C virus (HCV) genotype (GT) 1 infection live in East Asia. This study evaluated the efficacy, pharmacokinetics, safety, and tolerability of simeprevir plus peginterferon alpha‐2a and ribavirin (PR) in HCV GT1‐infected, treatment‐naïve, Asian patients with compensated liver disease. Methods: This phase III, randomized study (NCT01725529) was conducted in China and South Korea. Patients received simeprevir 150 mg once daily (QD), simeprevir 100 mg QD, or placebo, in combination with PR for 12 weeks. Patients in the simeprevir groups received PR alone for a further 12 or 36 weeks based on response‐guided treatment criteria. Patients in the placebo group received a further 36 weeks of PR alone. The primary efficacy endpoint was sustained virologic response 12 weeks after planned end of treatment (SVR12). Secondary endpoints were safety, pharmacokinetics, tolerability, and patient‐reported outcomes. Results: Overall, 457 patients were treated; the majority had GT1b infection (452/457 [99%]) and IL28B CC GT (364/457 [80%]). Of the 454 patients who had liver biopsy, 26 had cirrhosis (6%). SVR12 rates were superior for both the simeprevir 100 mg (89%; P = 0.003) and 150 mg (91%; P < 0.001) groups versus placebo (76%). Adverse events were mainly grade 1/2 and occurred at a similar incidence across all treatment groups. Overall, eight patients (2%) discontinued simeprevir or placebo treatment because of adverse events. Conclusions: Both simeprevir (100 mg and 150 mg QD) plus PR achieved superiority in SVR12 versus placebo plus PR in treatment‐naïve, HCV GT1‐infected, Asian patients and were well tolerated.